Patterns of Antihypertensive Drug Prescribing and Refill Adherence Among BPJS Referral-Back Patients: A Study at Pharmacy “X”, Pontianak - Isnindar Isnindar; Shahiroh Haulaini Shahiroh Haulaini; Hestiva Hestiva; Berlian Rizky Putra (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
High blood pressure often develops without obvious symptoms, causing many individuals to remain unaware of the condition until organ damage has already occurred. The absence of noticeable signs makes hypertension a major contributor to the increasing incidence of complications within the cardiovascular system. It has become a government priority to control hypertension through the National Health Insurance Program (JKN) BPJS, particularly the Referral Back Program (Program Rujuk Balik/PRB). This study aims to describe medication refill adherence and prescribing patterns of antihypertensive drugs among BPJS Kesehatan participants at “X” Pharmacy, Pontianak. This research employed a descriptive observational design with retrospective data from prescriptions and the Pharmacy–BPJS application for the period of October 2025. The analyzed data included sex, age, and the types of antihypertensive therapy used. Adherence was asessed using the Medication Possession Ratio (MPR) method. The results showed that medication refill adherence among PRB patients at Pharmacy “X” was predominantly in the adherent category. The most frequently prescribed antihypertensive drug was candesartan, an angiotensin receptor blocker (ARB), with a tendency toward combination therapy. Most patients were within the 60–75 age group and were predominantly female. In conclusion, medication refill adherence among PRB antihypertensive patients was generally good, supporting long-term therapeutic effectiveness. The prescribing patterns observed were largely consistent with clinical practice guidelines for hypertension management. Continuous education and monitoring are recommended to further improve adherence and therapeutic outcomes.